Proposed Singapore-India free trade agreement : business opportunities for a leading third party logistics provider. - Kim, Eun Jeong. (2008)
An examination of which industry sectors will have business opportunities from FTA if it is concluded between Singapore and India, and also what service offerings these industry sectors could expect from logistics service providers.